Organizational Commitment Drives Safety Culture Outcomes - Muhamad Abdul Jumali; Anita Kristina; Rusdiyantoro Rusdiyantoro (Jurnal Teknik Industri, 2026)
This study addresses the lack of integrated frameworks explaining how organizational safety culture influences individual safety behavior in small-scale industrial settings. The research aims to develop a structural model where organizational commitment mediates the relationship between safety culture and safety behavior. A quantitative survey was conducted in a briquette manufacturing firm involving 130 production workers. Data were collected using validated questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS software. The model demonstrated satisfactory fit indices (CFI = 0.957; RMSEA = 0.059), and mediation analysis via bootstrapping confirmed that organizational commitment fully mediates the effect of safety culture on behavior. These findings highlight that improving safety behavior requires more than formal procedures; it depends on the internalization of shared cultural values through commitment. The study contributes to the development of diagnostic and intervention models for enhancing worker safety in labor-intensive industrial settings.